Leptin independently predicts development of sepsis and its outcome - Sofie Jacobsson; Peter Larsson; Göran Johansson; Margareta Norberg; Göran Wadell; Göran Hallmans; Ola Winsö; Stefan Söderberg (BMC, 2017)
Abstract Background Sepsis is a life-threatening condition and obesity is related to the clinical outcome. The underlying reasons are incompletely understood, but the adipocyte derived hormones leptin and adiponectin may be involved. Methods Patients aged 18 years or more with documented first time sepsis events were included in a nested case-referent study if they had participated in previous health surveys. Two matched referents free of known sepsis were identified. Circulating levels of leptin and adiponectin were determined in stored plasma, and their impact on a future sepsis event and its outcome was evaluated. Results We identified 152 patients (62% women) with a sepsis event and a previous participation in a health survey. Eighty-three % had also blood samples from the acute event. Hyperleptinemia at health survey associated with a future sepsis event (OR 1.77, 95% CI 1.04-3.00) and with hospital death. After adjustment for BMI leptin remained associated with sepsis in men, but not in women. High levels in the acute phase associated with increased risk for in hospital death in women (OR 4.18, 95% CI 1.17-15.00), while being protective in men (OR 0.05, 95% CI 0.01-0.48). Furthermore, leptin increased more from baseline to the acute phase in men than in women. Adiponectin did not predict sepsis and did not relate to outcome. Conclusions Hyperleptinemia independently predicted the development of sepsis and an unfavourable outcome in men, and inertia in the acute response related to worse outcome.